Mesenchymal Stem Cell Therapy and New Approaches in Covid-19 Patients - Özkan, Serbay; Koyutürk, Meral (Cerrahpaşa Medical Journal, 2020)
The new type of coronovirus-borne infection, which appeared in Wuhan, Chine in late December 2019, has turned into a rapidly spreading worldwide pandemic. The disease caused by this new type of coronavirus has been officially announced by the World Healty Organization as Covid-19 (Coronovirus disease-19). The clinical spectrum of Covid-19 manifests variations as including respiratory distress syndrome (ARDS) in which ventilation support is required, sepsis, septic shock and multiple organ failure syndrome and may result in high mortality especially in the elder patients and/or in chronic disease. Although drug and research laboratories around the world have started vaccination and treatment development studies for the new type of coronavirus, it is forseen that these studies will take months to complete. This situation made it indispensable to seek alternative and urgent solutions that may be effective in the treatment of the disease. When the pathogenesis of the disease was examined, it was seen that systemic damage caused by cytokin storm resulted from excessive reaction of the immune system is very important. Therefore; taking under control of over-activated immune systems of Covid-19 infected patients was thought to be effective in the treatment of the disease and mesenchymal stem cells (MSCs) which are chracterized with prominent strong immunomodulatory capacity were started to be applied for the treatment and the positive results were obtained. Even though the treatment protocols and clinical application criterias for MSCs in Covid-19 infections have not yet been regulated, the first results have indicated that MSCs have significant promising therapeutic potential. Cite this article as: Özkan S, Koyutürk M. Mesenchymal Stem Cell Therapy and New Approaches in COVID-19 Patients. Cerrahpaşa Medical Journal 2020; 44(2): 57-64.